Echocardiographic evaluation of simple versus complex congenital heart disease in a tertiary care Paediatrics Hospital - Sarkar, Uttam Kumar; Chatterjee, Anish; Basu, Suprit; Pan, Atanu; Periwal, Sumit (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Congenital heart diseases are treatable either by catheter based intervention or open heart surgery according to their quality. In our study we aim to analyze congenital heart disease echocardiographically into simple versus complex heart disease at a tertiary care centre with a public health planning and policy making perspective. Materials & Methods: This hospital based study was done on 1010 patients, both from in-patient and out-patient, who were clinically suspected to have heart disease from January 2015 to September 2016 at Dr.B.C.Roy P.G.I.P.S. Kolkata and echocardiographically categorized. Results: A VSD was the commonest acyanotic heart disease (17. 08%).Tetralogy of Fallot (TOF) was commonest complex cyanotic heart disease (10.64%), VSD +ASD was the commonest combined lesion (8.12%). Simple heart lesions (63.1%) were commoner than complex (36.9%) congenital heart diseases. Conclusion: Health policy makers should give due care to manage Congenital Heart Disease either catheter based or surgically keeping in mind about 63.1% of the lesions are simple cardiac lesions and 36.9% lesions are complex cardiac lesion where complex surgery is required.